Leverage, Corporate Governance, and Financial Distress: Evidence from Basic Chemicals Companies Listed on the Indonesia Stock Exchange - Lila Shafrila Arifin; Umiaty Hamzani; Syarif M. Helmi (Jurnal Investasi Islam, 2026)
This study examines the effect of leverage and corporate governance, proxied by managerial ownership and institutional ownership, on financial distress in Basic Chemicals companies listed on the Indonesia Stock Exchange (IDX) during 2022–2025. Previous studies have reported inconsistent findings regarding the influence of leverage and ownership structure on financial distress, while evidence focusing specifically on the Basic Chemicals industry remains limited. This research addresses this gap by providing empirical evidence from a capital-intensive sector with unique financing characteristics in the post-pandemic period. The study employed a quantitative approach using secondary data obtained from annual reports and financial statements. A purposive sampling technique was applied to select 16 companies, resulting in 64 firm-year observations. Financial distress was measured using the Altman Z-Score and transformed into a dummy variable, while logistic regression was used for data analysis. The results indicate that leverage has no significant effect on financial distress, suggesting that debt utilization remains at a manageable level. In contrast, managerial ownership and institutional ownership have a positive and significant effect on financial distress, implying that ownership concentration alone does not guarantee effective corporate governance or lower financial distress risk. The study contributes to Agency Theory by demonstrating that ownership structure requires effective monitoring mechanisms to mitigate agency conflicts. Practically, the findings provide useful insights for corporate managers, investors, and regulators in strengthening governance practices, improving ownership monitoring, and developing strategies to reduce the risk of financial distress.